2015
DOI: 10.1097/acm.0000000000000591
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Workforce Shortages and Career Recommendations From Practicing Clinicians

Abstract: Efforts to solve the primary care workforce shortage that ignore the significant dissatisfaction of PCPs with their own careers are unlikely to be successful. Simply adding training slots and increasing reimbursement rates will do little to solve the problem if PCPs continue to view their own careers as ones they cannot recommend to others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…A study conducted in the United States within the context of the private PHC system showed that the generation of innovative actions was indicative of professional satisfaction, knowledge employed in daily practices, and procedures based on therapeutic care and patient-centered comprehensive and decisive actions (10) . Some of these actions were also reported by the nurses in the present study as reasons to work in PHC, as well as the positive impact perceived in the lives of their patients.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in the United States within the context of the private PHC system showed that the generation of innovative actions was indicative of professional satisfaction, knowledge employed in daily practices, and procedures based on therapeutic care and patient-centered comprehensive and decisive actions (10) . Some of these actions were also reported by the nurses in the present study as reasons to work in PHC, as well as the positive impact perceived in the lives of their patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cost-effective strategies are needed to address this problem. Primary care practitioners are the first line for both primary and secondary obesity prevention efforts but must be equipped with adequate tools, training, and capacity to provide appropriate care [10–14]. Large-scale trials such as the Diabetes Prevention Program [15] and the Look-AHEAD [16] trials have been shown to be effective in achieving sustained weight loss, following a frequent, structured behavioral intervention.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Remote and distant communities demonstrate higher rates of the five leading causes of death in the United States, 5,6 attributed, in part, to the lack of resources 2,5 in the ambulatory setting, 7 limited access to specialists and specialized resources, fewer transportation options, and socioeconomic disparities. [8][9][10][11][12] Rural healthcare is especially problematic in vulnerable populations, including persons with disabilities, 13 children, 14 and older adults. 11 Information and communication technologies provide an opportunity to improve rural healthcare delivery in older adults, the fastest growing user group of technology, 15 particularly in an era of burgeoning rural broadband and cellular connectivity.…”
mentioning
confidence: 99%